2017
DOI: 10.1038/s41598-017-05067-9
|View full text |Cite
|
Sign up to set email alerts
|

On the influence of interface charging dynamics and stressing conditions in strained silicon devices

Abstract: The performance of strained silicon devices based on the deposition of a top silicon nitride layer with high stress have been thoroughly analyzed by means of simulations and experimental results. Results clearly indicate that the electro-optic static response is basically governed by carrier effects. A first evidence is the appearance of a variable optical absorption with the applied voltage that should not occur in case of having a purely electro-optic Pockels effect. However, hysteresis and saturation effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…Other works, some of which were based on high frequency measurements, questioned the interpretation of these experiments. They demonstrated that frozen charges at the Si/SiN interface determine an abundance of free-carriers in the waveguide, causing a large DC electro-optic effect due to free carrier dispersion 1215 . In particular, an upper limit of 8 pmV −1 to the value of the strain-induced χ (2) was set 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Other works, some of which were based on high frequency measurements, questioned the interpretation of these experiments. They demonstrated that frozen charges at the Si/SiN interface determine an abundance of free-carriers in the waveguide, causing a large DC electro-optic effect due to free carrier dispersion 1215 . In particular, an upper limit of 8 pmV −1 to the value of the strain-induced χ (2) was set 13 .…”
Section: Introductionmentioning
confidence: 99%
“…By applying an electric field to a silicon waveguide, the free-carrier concentration and distribution are indeed changed, which results in a variation of the refractive index due to the plasma-dispersion effect 20,21 . Furthermore, it has been reported that the linear electro-optic effect detected in strained silicon waveguides was induced by charging centers in the SiN stress overlayer, which moves the silicon waveguide directly into an inversion regime, where the electron concentration grows linearly with the voltage [22][23][24] . This result has deep consequences for the interpretation of the electro-optic effect in strained silicon waveguides, particularly in the conclusion that there are two main electro-optic (EO) effects that jointly contribute to the total change in effective mode index (Δn eff ) in a strained silicon waveguide.…”
mentioning
confidence: 99%
“…Most of these attempts have been based on the deposition of a stressing silicon nitride cladding layer to strain the silicon waveguide and, consequently, to break the silicon centrosymmetry [10]. Even though positive results have been reported [10,11], very recent works demonstrate that most of the reported measurements have been misinterpreted [12][13][14][15]. The χ (2) that can be induced in silicon by the strain is very low [16,17].…”
Section: Introductionmentioning
confidence: 99%